2013
DOI: 10.1001/jamapediatrics.2013.2572
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics to Prevent or Treat Excessive Infant Crying

Abstract: IMPORTANCE Excessive infant crying is common, distressing, but without proven effective prevention or management options. Probiotics may be a promising solution. OBJECTIVE To examine whether probiotics are effective in the prevention/management of crying ("colic") in infants 3 months or younger. DATA SOURCES A systematic search of MEDLINE, EMBASE, and the Cochrane Library, supplemented by the metaRegister of Controlled Trials. STUDY SELECTION Studies that randomized infants 3 months or younger to oral probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 37 publications
0
81
0
4
Order By: Relevance
“…To date, there are a few reviews on probiotic effects on infantile colic, which may reflect peripheral nervous system action, and one recent study reviewing only human studies. [64][65][66] Similarly, among the 56 RCTs so far which tested probiotics in adults with IBS that have or have not shown effects on peripheral (bowel) functions, 15 none have investigated whether any CNS effect was affected or improved. We identified studies applying probiotics as single-or multiple-strain preparations in animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are a few reviews on probiotic effects on infantile colic, which may reflect peripheral nervous system action, and one recent study reviewing only human studies. [64][65][66] Similarly, among the 56 RCTs so far which tested probiotics in adults with IBS that have or have not shown effects on peripheral (bowel) functions, 15 none have investigated whether any CNS effect was affected or improved. We identified studies applying probiotics as single-or multiple-strain preparations in animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] A recent meta-analysis of three small, randomised controlled trials of breastfed infants with colic reported that Lactobacillus reuteri noticeably reduced crying time at 21 days post supplementation. 31 However, one trial was unblinded, 32 two included only infants with mothers on dairy-free diets, 32 33 and none used validated measures of infant distress. No trials have included formula fed infants, which is relevant because colic is associated with early breastfeeding cessation.…”
Section: Introductionmentioning
confidence: 99%
“…44 Estudios recientes han mostrado una diferencia en la microbiota de lactantes con y sin cólico [45][46][47] lo que podría explicar los cambios que causa esta patología: inflamación, producción de gas, distensión y alteración en la motilidad intestinal. 48 En una revisión sistemática realizada por Valerie Sung y sus colegas, en un meta-análisis de tres estudios, se encontró una marcada reducción en el llanto en un tiempo de 21 días en pacientes alimentados al seno materno con cólico infantil utilizando Lactobacillus reuteri; 49 sin embargo, se concluye que aún deben hacerse más estudios al respecto.…”
Section: Cólico Infantilunclassified